Methodology and application of multiplex PCR-dipstick DNA chromatography for the detection of eight respiratory bacterial pathogens - Hu, Liuyang; Wang, Xiuri; Li, Qiong (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundCommunity-acquired pneumonia is primarily caused by Acinetobacter baumannii, Pseudomonas aeruginosa, Klebsiella pneumoniae, Streptococcus pneumoniae, Haemophilus influenzae, Staphylococcus aureus, Mycoplasma pneumoniae, and Chlamydia pneumoniae, leading to severe illness and death in developing countries.MethodsA rapid, straightforward, sensitive, high-throughput, and precise multiplex PCR-dipstick DNA chromatography assay was devised. This innovative technique was specifically engineered for the immediate and efficient detection of the aforementioned eight respiratory pathogens, with particular emphasis on scenarios involving co-infections. Custom-designed specific primers were employed, wherein the 5′ end of the forward primers was tagged with oligonucleotide tags (Tag) and the 5′ end of the reverse primers was conjugated with biotin. A C3 spacer was incorporated to bridge the Tag and the forward primer. Complementary oligonucleotides (cTag) corresponding to each of the eight pathogens were immobilized within the test area of the test strip. Meanwhile, biotin was strategically utilized to create an internal control line at the distal end of the test strip. The biotin moiety at the 5′ end of the reverse primer was engineered to interact with blue latex microspheres coated with streptavidin, thereby triggering a detectable signal. Following the PCR amplification of the target DNA fragments, during the membrane strip chromatography hybridization process, the Tag- and biotin-labeled target DNA engaged in a dual interaction. First, it bound to the blue latex microspheres via streptavidin–biotin binding, and second, it hybridized with the cTag on the membrane strip. This led to the accumulation of captured blue latex microspheres at both the test line and the internal control line, manifesting as visible blue bands. A total of 186 respiratory sputum or bronchoalveolar lavage fluid specimens were collected and analyzed. The multiplex PCR-dipstick DNA chromatography assay was deployed for detection, while traditional bacterial culture was also carried out in parallel for comparative purposes. To rigorously validate the accuracy of the multiplex PCR-dipstick DNA chromatography assay in identifying PCR products, DNA sequencing was performed on all PCR products derived from the clinical samples.ResultsThe multiplex PCR-dipstick DNA chromatography assay demonstrated remarkable efficacy, being capable of specifically discriminating among the eight pathogens within a remarkably short timeframe of 40 minutes. The detection limit for individual bacterial species ranged from 10 to 102 CFU/mL. Notably, no cross-reactions were observed among the eight target bacteria, nor with other representative respiratory bacteria, including Acinetobacter junii, Enterobacter cloacae, Klebsiella oxytoca, Haemophilus parainfluenzae, Pseudomonas fluorescens, Aeromonas hydrophila, and Staphylococcus epidermidis. The concordance between the results obtained from the multiplex PCR-dipstick DNA chromatography assay and those from DNA sequencing was absolute, with a kappa value of 1.00.ConclusionA successful multiplex PCR-dipstick DNA chromatography assay was established for the simultaneous detection of eight respiratory bacterial pathogens and was effectively applied in clinical sample analysis. This indicates that this single-use device has promising potential for analyzing the microbial composition related to respiratory infections and is also suitable for small laboratories and field diagnostics.